EDUKASI KEWIRAUSAHAAN BAGI ANAK PANTI ASUHAN MELALUI PEMANFAATAN LIMBA KULIT JERUK PURUT MENJADI LATANY - Sagajoka, Estherlina; Nona, Reyna Virginia; Mantaria, Stefania (LPPM Universitas Flores, 2025)
This community service activity aims to provide entrepreneurial education for children at the Brayat Pinuju Detusoko orphanage, teaching them to make Anti-Mosquito Aroma Therapy Candles (latany) using recycled candles and orange-peel waste. Used candles are made from basic materials, while orange peel waste serves as a source of natural aroma, acting as a repellent for mosquitoes and other insects. The process of making aroma therapy candles by melting used candles, adding orange peel waste, essential oils, eucalyptus oil, molto, food colouring and moulding candles using mini glass containers. The results obtained are that the aroma therapy candles produced have a strong aroma and can repel mosquitoes. As a more economical room freshener, because the litany container is glass, this candle can be used many times, and if the wick runs out, it can be replaced with a new wick and can be used again. And the candles produced have a fairly promising selling value for increasing income, both personally and in groups. Latany is a multi-function candle, as a candle for lighting, a room freshener, mosquito repellent. which is effective, efficient, friendly to health and has economic value.